Predicting clinical entry point for thoracic epidural catheter insertion during paramedian approach: A prospective observational study - Bhakti Y. Deshmukh; Madhavi G. Shetmahajan; Sumitra G. Bakshi; Parmanand Jain (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: Thoracic epidural insertion has high failure rates in the mid-thoracic region due to steep angulation of oblique bending of spinous processes. The preferred skin puncture point for epidural needle insertion in the paramedian sagittal plane with respect to the superior/inferior tip of spinous process or inter-spinous cleft in the mid-thoracic region (T5-8) is not standard. The primary objective of this prospective observational study was to find the skin puncture point which had the best success rate for a successful epidural catheterization. Secondary objectives were to study the number of attempts and passes required to locate epidural space, incidence of failed epidural, and its relationship with patient characteristics and demographics. Material and Methods: After informed consent, 155 patients planned for general anesthesia with epidural analgesia in the mid-thoracic region were included in the trial. Patient demographics, the details of epidural attempts with respect to anatomical landmarks, distance from the midline, and number of passes in each attempt were noted. Epidural catheterization was considered successful after demonstrating dermatomal band of sensory blockade. Results: The success rate at different skin puncture sites was not statistically significant (P = 0.58). We found a failure rate of 12.9%. Failed epidural catheterization was significantly high in the age group >56 years (n = 62 and P = 0.007). Conclusion: In our study, none of the skin puncture points had a significant association with successful epidural insertion in mid-thoracic segments using a para-median approach.